2021
DOI: 10.1186/s12939-021-01582-4
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of racial/ethnic and socioeconomic disparities in COVID-19

Abstract: Background Preliminary evidence from the COVID-19 pandemic shows the presence of health disparities, especially in terms of morbidity and mortality. This study aimed to systematically review the evidence on the association of racial/ethnic and socioeconomic status (SES) with health outcomes and access to healthcare services during the COVID-19 pandemic. Methods We retrieved published evidence from late December 2019 through March 1, 2021. The targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
249
5
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(273 citation statements)
references
References 87 publications
16
249
5
3
Order By: Relevance
“…The increase in mortality risk was as twice as high, in COVID-19+ subjects who recovered from viral infection, when compared with those without any prior documented exposure to SARS-CoV-2. This excess risk of mortality was, as expected, related to co-variates such as aging, lower socio-economic status, presence of co-morbidities or to male sex [1] , [18] , [19] . It is noteworthy to stress that a higher deprivation index is related with an about 20-25% increase in mortality risk: this could be due to the higher risk exposure to COVID-19 in lower socio-economic strata of the population [20] .…”
Section: Discussionsupporting
confidence: 77%
“…The increase in mortality risk was as twice as high, in COVID-19+ subjects who recovered from viral infection, when compared with those without any prior documented exposure to SARS-CoV-2. This excess risk of mortality was, as expected, related to co-variates such as aging, lower socio-economic status, presence of co-morbidities or to male sex [1] , [18] , [19] . It is noteworthy to stress that a higher deprivation index is related with an about 20-25% increase in mortality risk: this could be due to the higher risk exposure to COVID-19 in lower socio-economic strata of the population [20] .…”
Section: Discussionsupporting
confidence: 77%
“…Accordingly, US communities characterized by both high racial and ethnic diversity as well as high socioeconomic diversity are of particular interest for examining the differential contributions of race and ethnicity and socioeconomic factors to health disparities. As a novel, widespread, and contemporaneous disease entity with discrete onset, the COVID-19 pandemic provides a unique and invaluable opportunity to study racial inequities in health care delivery and outcomes in the US [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, including a systematic review examining differences in COVID-19 outcomes by race/ethnicity, have found a similar pattern in disparities, in which Black or Hispanic patients face higher hospitalization and mortality rates. [ 20 , 22 25 ] Yet other studies have reported no racial/ethnic differences in case-fatality mortality rates. [ 20 , 26 , 27 ] Despite these differences in findings related to mortality, the literature has consistently shown increased risk of severe illness in racial/ethnic minority populations.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 , 26 , 27 ] Despite these differences in findings related to mortality, the literature has consistently shown increased risk of severe illness in racial/ethnic minority populations. [ 25 ] In our study sample, Black and Hispanic patients were more likely to be enrolled in VOU compared to being discharged home without additional care. This suggests that even among those cared for in outpatient settings, there was higher disease severity (based on care level) compared to White patients.…”
Section: Discussionmentioning
confidence: 99%